Interpersonal Communication Dynamics in Religious Rehabilitation: Analyzing Inclusion, Control, and Affection in an Indonesian Youth Community - Mukhamad Ainul Yaqin; Abdurrosyid Rizi Ramadhan (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2026)
The failure of punitive approaches to youth delinquency necessitates humanistic, community-based rehabilitation models. The Pemuda Insyaf Karanganyar (KOPIKA) community offers a unique approach to rehabilitating street subcultures through interpersonal da'wah. This study analyzes the leader's communication dynamics using FIRO-B theory (Inclusion, Control, Affection). Employing an intrinsic qualitative case study design, data were collected via in-depth interviews and participant observation of members with at-risk backgrounds, followed by thematic analysis. Results reveal that behavioral transformation is driven by three mechanisms: (1) Radical Inclusion, offering unconditional acceptance to foster a sense of belonging; (2) Persuasive Control, shifting from hierarchical authority to active participation; and (3) Deep Affection, acting as an emotional anchor against recidivism. The study concludes that in collectivist contexts, fulfilling psychosocial needs (inclusion and affection) is a prerequisite for religious compliance (control). This research proposes an adaptive, empathy-based da'wah model for marginalized groups.